21st century trucking: A trajectory for ergonomics and road freight. (March 2016) - Bedinger, M.; Walker, G.H.; Piecyk, M.; Greening, P.
Abstract: Over the past decade there has been significant pressure to minimise emissions and safety risks related to commercial driving. This pressure to meet the triple bottom line of cost, environment, and society has often resulted in the rapid application of vehicle technologies designed to mitigate undesired effects. Often the cognitive and behavioural effects of technologies on the commercial driver have not received in-depth analysis to determine comprehensive viability. As such, this paper aims to identify a timescale for implementation for future technologies for UK road freight, and likely associated human factors issues, improving upon the currently employed 'trial-and-error' approach to implementation which may carry high economic, environmental, safety-related risk. Thought experiments are carried out to broadly explore these future systems. Furthermore, this work aims to examine whether technology alone will be enough to meet future CO2 reduction targets, and assess the role of behavioural and systems interventions for future research. Highlights: Addressing the 'triple bottom line' (TBL) is key for sustainable road freight. Ergonomics and logistics have rarely intersected in research. Results present a technology & human factors roadmap for commercial vehicles to 2050. Technology alone is not enough to achieve future CO2 targets. Ergonomics research in commercial driver behaviour is crucial in meeting the TBL.